A companion to the Reformation in Scotland, ca. 1525-1638 frameworks of change and development - Hazlett, Ian 1944- (Brill's companions to the Christian tradition, 2022)
"This book presents customized chapters by 28 authors on the Scottish Reformation from the late 1520s to 1638. The book has broad thematic frameworks into which the specific chapters fit. There are 10 such major themes, namely: external and internal pressures for change; breakthrough and revolution; theological and philosophical formulations; varieties of dissemination; humanism and higher education; legal systems and moral order; appropriations in literary and popular cultures; outsiders; evolution of new national identity; historiographical traditions and prospective developments. While there are introductory elements, the chapters both recall previous studies and offer new research. Concerns of the book are to recall Reformation core religious dimensions and to highlight Scottish contribution to the rich tapestry of the Reformation in Europe."